TRANSFORMASI DIGITAL DAN PENGARUHNYA TERHADAP BUDAYA ORGANISASI: TINJAUAN LITERATUR SISTEMATIS - Fahmi, Teuku (Jurnal Manajemen Akuntansi dan Ilmu Ekonomi, 2024)
Digital transformation has become a global phenomenon reshaping how organizations in Indonesia operate and compete. This study aims to analyze the impact of digital transformation on organizational culture through a systematic literature review (SLR), focusing on aspects of collaboration, structural flexibility, resistance to change, and value adaptation. The results indicate that digital transformation enhances collaboration and flexibility within organizations, fostering better cross-departmental communication and responsiveness to market changes. However, resistance to change emerges as a significant challenge, particularly among employees concerned about their roles. Adapting organizational values towards a more open and innovative culture also requires continuous support from leadership. In conclusion, the success of digital transformation depends on a holistic and comprehensive change management approach. This study provides guidance for organizations to design cultural strategies that support the sustainability of digital transformation in Indonesia.